(Mis)representation of the LGBT community through nomination and categorisation: the case of Nur Sajat in The Star - Mohd Amirulfikri Roslani; Marlina Jamal (Penerbit Universiti Kebangsaan Malaysia, 2024)
The purpose of this study is to explore how the Malaysian newspaper The Star represents the LGBT community, specifically Nur Sajat, a local transgender woman, in their published news articles. This study employs van Leeuwen’s theory of representation of social actors to investigate how nomination and categorisation strategies are employed in portraying Nur Sajat. Previous studies related to the representation of the LGBT community have only focused on coverage and content released as opposed to looking at them as social actors per se. The study first gathered 29 news articles published by The Star from February 2021 to February 2022 as a corpus. Secondly, through Critical Discourse Analysis, the corpus then underwent nomination and categorisation analyses to identify how Nur Sajat is represented in terms of her unique and shared identities. The findings indicate that The Star misrepresents Nur Sajat through deadnaming and misgendering, which undermines her transgender identity. Despite portraying her as a successful businesswoman, negative depictions resembling criminal profiling are also highlighted. Media might better engage language associated with sensitivity and accuracy in line with legal and societal norms. Recognising diverse gender identities and sexual orientation converges ethical journalism; thus, media coverage might better comply with legal mandates and evolving societal attitudes. Finally, future research could expand on this study by comparing representation strategies of the LGBT community across various Malaysian media outlets.